Pelatihan Peningkatan Keterampilan Berbicara Bahasa Inggris Melalui Metode Task-Based Language Teaching Bagi Mahasiswa Ekonomi Syariah - Linda Septiyana; Aisyah Sunarwan; Silviana Gestiana; Bagus Firmansyah (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2021)
Islamic Economics Department makes English as a basic subject so that the students can have basic skills in English. Having the ability to communicate English well of course becomes a precious value for their careers ahead considering that now days we come to the Era of the Asean Economic Community (AEC). The objectives of this community service activity are 1) introducing the Task-Based Language Teaching (TBLT) learning method to Islamic Economics Students of IAIN Metro; 2) improving the English speaking skills of Islamic Economics students at IAIN Metro. The target of this Community Service Activity is Islamic Economics Students (ESy) IAIN Metro. The methods used in this service are observations, interviews, and conducting training. The conclusions of this activity shows that 1) there is an improvement in knowledge and understanding of Islamic Economics students of IAIN Metro about Task-Based Language Teaching (TBLT) learning method and 2) there is an improvement of Islamic Economics students’ skills in speaking English.